Membenahi Hubungan Manusia dengan Lingkungan Hidup dalam Perspektif Metafisika Whitehead : Fixing Human Relations with the Environment in Whitehead's Metaphysical Perspective - Nugroho, Yohanes Dwi (Undiksha, 2025)
The focus of this study is to explore the relationship between humans and nature from the metaphysical perspective of Alfred North Whitehead. This is based on the fact that the living environment is not doing well. Humans are faced with the problem of the ecological crisis. Technological developments and advances have changed the pattern of relationships between humans and the environment. Humans use the environment not only to support their lives, but also to gain profits and fulfill their ambitions. Therefore, in this article, the author tries to explore the ideal relationship between humans and the environment from the perspective of process philosophy developed by Whitehead. From there it was discovered that all entities are always changing, including human lifestyles. This needs to encourage humans to change their relationship patterns with the environment so that nature remains sustainable and can provide benefits for future generations. Humans need to be aware that they are an integral part of their environment and that the environment has an intrinsic value within itself that every human being needs to respect. The research method used is a qualitative method in the form of a literature study. The author looks at Whitehead's thoughts in his book and sees their connection to the theme of this article with the help of other appropriate library sources.